Enhancing English For Nursing: A Comprehensive Needs Analysis For Effective Communication In Emergency Nursing Study Programs - SB, Handayani (Universitas PGRI Sumatera Barat, 2023)
students enrolled in nursing study programs with a focus on emergency characteristics. The investigation encompasses both target needs and learning needs, emphasizing the specific language requirements in the nursing field. English for Nursing falls under the domain of English for Specific Purposes (ESP), designed to cater to learners' specific language needs, fostering more effective and comprehensive teaching and learning. By aligning English instruction with the demands of the nursing discipline, non-English program students will gain familiarity with English tailored to nursing contexts. The ESP approach aims to address the specific language acquisition challenges faced by learners with distinct objectives. Data collection involves questionnaires administered to 45 students and direct interviews with emergency nursing lecturers. Findings reveal the significance of learning English for improved communication within the context of conversations or practical applications. The identified English materials concentrate on terms relevant to nursing study programs, particularly those associated with emergency characteristics, becoming the focal points of instruction. Additionally, materials focusing on enhancing listening and speaking skills emerge as key priorities in the learning process. The outcomes of this study are anticipated to serve as a valuable reference for the design and development of syllabi, specifically tailored to English for Nursing courses.